Mechanisms of Cancer Cell Lymphatic Endothelialization in Tumor Lymphangiogenesis and Metastasis: A Comprehensive Review - Wang J; Hu Z; Qian X; Xin W; Cai W; Tang J (Journal of Inflammation Research)
Jingwen Wang,1 Zhandong Hu,1 Xuejiao Qian,2 Weiwei Xin,1 Wenjuan Cai,1 Jianwu Tang3 1Department of Pathology, Tianjin First Central Hospital, School of Medicine, Nankai University, Tianjin, People’s Republic of China; 2Department of Respiratory medicine, Tianjin First Central Hospital, School of Medicine, Nankai University, Tianjin, People’s Republic of China; 3Department of Pathology, Dalian Medical University, Key Laboratory for Tumor Metastasis and Intervention of Liaoning Province, Dalian, Liaoning, People’s Republic of ChinaCorrespondence: Jianwu Tang, Department of Pathology, Dalian Medical University, Key Laboratory for Tumor Metastasis and Intervention of Liaoning Province, No. 9 West, Lvshun Southern Road, Lvshunkou District, Dalian, Liaoning, 116044, People’s Republic of China, Email tang2323jianwu@126.com Wenjuan Cai, Department of Pathology, Tianjin First Central Hospital, School of Medicine, Nankai University, No. 2 Baoshan Road, Xiqing District, Tianjin, 300192, People’s Republic of China, Email wenjuancai_cwj@126.comAbstract: Cancer cell lymphatic endothelialization refers to the transformation of cancer cells into lymphatic endothelial cells through complex cellular and molecular mechanisms, which involve transdifferentiation of cancer cells and their fusion with endothelial cells, both modulated by multiple signaling pathways. This process reflects a dual phenotype comprising features of both cancer cells and lymphatic endothelial cells. The expression of lymphatic-specific markers, including PDPN, LYVE1, PROX1, and SOX18, serves as molecular evidence of this process. Histopathologically, this phenomenon is manifested through lymphangiogenic mimicry, which can be classified into lymphatic-like, mosaic, and lymphatic types. This study presented a theoretical framework to elucidate the developmental mechanisms driving cancer cell lymphatic endothelialization and provided a new theoretical basis for understanding the cellular origin of tumor-associated neolymphatic vasculature and introduces new pathways for investigating mechanisms of tumor lymphangiogenesis and metastasis, thereby providing potential avenues for clinical treatment strategies.Keywords: cancer cell lymphatic endothelialization, lymphangiogenesis molecules, lymphangiogenic mimicry, tumor lymphangiogenesis, tumor lymphatic metastasis